Increased food availability raises eviction rate in a cooperative breeding mammal. (12th April 2017) - Dubuc, C.; English, S.; Thavarajah, N.; Dantzer, B.; Sharp, S. P.; Spence-Jones, H. C.; Gaynor, D.; Clutton-Brock, T. H.
Abstract : In group-living mammals, the eviction of subordinate females from breeding groups by dominants may serve to reduce feeding competition or to reduce breeding competition. Here, we combined both correlational and experimental approaches to investigate whether increases in food intake by dominant females reduces their tendency to evict subordinate females in wild meerkats ( Suricata suricatta ). We used 20 years of long-term data to examine the association between foraging success and eviction rate, and provisioned dominant females during the second half of their pregnancy, when they most commonly evict subordinates. We show that rather than reducing the tendency for dominants to evict subordinates, foraging success of dominant females is positively associated with the probability that pregnant dominant females will evict subordinate females and that experimental feeding increased their rates of eviction. Our results suggest that it is unlikely that the eviction of subordinate females serves to reduce feeding competition and that its principal function may be to reduce reproductive competition. The increase in eviction rates following experimental feeding also suggests that rather than feeding competition, energetic constraints may normally constrain eviction rates.